FAKTOR-FAKTOR YANG MEMPENGARUHI PEMANFAATAN PUSKESMAS DI KABUPATEN MUARO JAMBI - , Yani Sriningsih; , Ir. Leksono Probo Subanu, MURP., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The utilization of health centers as a health facility is indicated by the number of visits to the clinic. Health centers in the Muaro Jambi District are distributed in each district. Planning needs to consider the spatial distribution of the health centers and outreach centers so that the utilization can be optimized. This study aimed to determine factors affecting the utilization of health centers by mapping the patient visits and the spread of health centres locations. This research used deductive method with descriptive analytic. Research variables are location of health centers, number of visits, accessibility, health and outreach services. Data were analized using descriptive analysis, analytic and nearest neighbor analysis. The study found that the spatial distribution of the health centers in the Muaro Jambi District was clustered with the Nearest Neighbor Index value of 0.69. There are 12 units of health centers have a high-level visits and 6 units of health centers have a low-level visits. The visits level and accessibility correlated (p = 0,012), while health workers and service coverage were not correlated with the level of visits (p> 0.05).